The Influence of Self-Control and Financial Literacy on the Use of Shopeepaylater Among Students in The Faculty of Economics and Business at Swadaya Gunung Jati University in Cirebon - Apriliani Putri, Mardiana; Dhea Parlina, Nurhana (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of Buy Now Pay Later (BNPL) services has transformed students' digital payment behavior, particularly through ShopeePayLater, which offers convenience, flexibility, and easy access to online credit. However, this development also raises concerns regarding uncontrolled consumption and students' ability to manage financial obligations responsibly. This study aims to examine the influence of self-control and financial literacy on the use of ShopeePayLater among students of the Faculty of Economics and Business, Universitas Swadaya Gunung Jati Cirebon. This research employed a quantitative associative approach with a survey method. The sample consisted of 115 active students who had used ShopeePayLater for at least three months, selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings show that self-control has a positive and significant effect on ShopeePayLater usage, indicating that students with better self-control tend to use the service more rationally and in a planned manner. Financial literacy also has a positive and significant effect, demonstrating that students with a stronger financial understanding are able to assess the benefits, risks, and payment mechanisms of the service more responsibly. This study concludes that self-control and financial literacy are important internal factors that support wiser and more responsible use of ShopeePayLater.